2023
DOI: 10.1177/07487304231177197
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype, Social Jetlag, and Nicotine Use

Abstract: Late chronotype, which often leads to higher social jetlag (SJL), is strongly associated with the prevalence of smoking. Any circadian disruption, strain, or misalignment, results in people not being able to live according to their biological time as is described by SJL, which we will therefore use as umbrella term. We hypothesized two scenarios potentially explaining the association between smoking and SJL: (A) If smoking delays the clock, circadian phase should advance upon quitting. (B) If people smoke more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
2
1
Order By: Relevance
“…Effects of both NMR and CPD on sleep traits were typically more prominent in current smokers than former smokers, suggesting that the effects of nicotine and smoking intensity on sleep traits are not long-lasting. In contrast to our findings, a recent study found that smoking cessation without nicotine replacement therapy did not affect chronotype, sleep quality or daytime sleepiness (Ghotbi et al, 2023). However, in that study sleep was assessed only 6 weeks after smoking cessation, which would not capture the long-term effects of cessation and the study was likely underpowered (n=49).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Effects of both NMR and CPD on sleep traits were typically more prominent in current smokers than former smokers, suggesting that the effects of nicotine and smoking intensity on sleep traits are not long-lasting. In contrast to our findings, a recent study found that smoking cessation without nicotine replacement therapy did not affect chronotype, sleep quality or daytime sleepiness (Ghotbi et al, 2023). However, in that study sleep was assessed only 6 weeks after smoking cessation, which would not capture the long-term effects of cessation and the study was likely underpowered (n=49).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have reported a higher prevalence of smoking among those with an evening chronotype (Ghotbi et al, 2023;Patterson et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation